1999
DOI: 10.1002/(sici)1097-4644(19991215)75:4<686::aid-jcb14>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the actin polymerization status as an apoptotic morphological effector in HL-60 cells

Abstract: The alterations of the cytoskeletal actin network have been implicated as a morphological effector in apoptosis. However, studies directly linking actin change to the morphological events in apoptosis are lacking. This study quantitatively examined the effect of actin alteration on the camptothecin (CPT)-induced apoptotic process in HL-60 cells. Actin alteration was induced by two distinctive types of agent: the polymerization-stimulating agent, Jasplakinolide (Jas), and the polymerization-blocking agent, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 32 publications
1
46
1
Order By: Relevance
“…The actin cytoskeleton was also involved in the apoptosis process, and alterations of actin polymerization had profound effects not only on apoptosis but also on cellular morphology. 45 The apoptotic process is accompanied by sequential cell morphology change, such as membrane blebbing, cell fragmentation, and apoptotic body formation. 45,46 Therefore, both actin polymerization alterations and cell morphology changes could be used as indicators for cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actin cytoskeleton was also involved in the apoptosis process, and alterations of actin polymerization had profound effects not only on apoptosis but also on cellular morphology. 45 The apoptotic process is accompanied by sequential cell morphology change, such as membrane blebbing, cell fragmentation, and apoptotic body formation. 45,46 Therefore, both actin polymerization alterations and cell morphology changes could be used as indicators for cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…45 The apoptotic process is accompanied by sequential cell morphology change, such as membrane blebbing, cell fragmentation, and apoptotic body formation. 45,46 Therefore, both actin polymerization alterations and cell morphology changes could be used as indicators for cell apoptosis. Since depolymerization of F-actin occurs during apoptosis, our findings suggested that 60 μM Zn 2+ could protect cells from apoptosis, while 140 μM Zn 2+ was likely to induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interference with actin dynamics by inhibition of its depolymerization enhances apoptotic activity in HL-60 cells [170, 171]. However, in T-cells disruption of the actin cytoskeleton promotes caspase-3-mediated apoptosis [172].…”
Section: Possible Physiological Pathological and Medical Implicamentioning
confidence: 99%
“…It is not yet clear, however, how the actin cytoskeleton is linked to the apoptotic machinery. For example, it has been demonstrated that actin polymerization is essential for the induction of apoptosis in endothelial cells [36] and in HL-60 cells [37,38]. On the other hand, in several other cell types, disruption of the cytoskeleton seems to trigger apoptosis [39][40][41].…”
Section: Introductionmentioning
confidence: 99%